Administration of pharmacological sleep aids prior to, during and following critical illness. Issue 11 (27th June 2022) - Wong, Cliff; Ho, Jankin; Ankravs, Melissa J.; Sharrock, Lucy; Kee, Kirk; Goldin, Jeremy; MacIsaac, Christopher; Presneill, Jeffrey J.; Ali Abdelhamid, Yasmine; Deane, Adam M.
Abstract: Background: Sleep in the intensive care unit (ICU) is frequently disturbed and this may have a detrimental effect on recovery. Aim: To determine the use of pharmacological sleep aids in critically ill patients prior to, during and after ICU admission. Methods: We conducted a single‐centre period prevalence study of all adult patients admitted to a university‐associated adult medical‐surgical ICU for more than two nights in a 3‐month period ending September 2019. The major outcome of interest was the proportion of ICU patients who had a pharmacological sleep aid administered prior to, during and after ICU admission. Associations of selected patient variables with sleep aid prescription in the ICU were summarised both as unadjusted univariable comparisons and as adjusted effect estimates returned by a multivariable logistic regression model. Results: During the study period, 370 patients met all eligibility criteria. A pharmacological sleep aid was identified prior to hospital admission in 34 (9%) patients and in 62 (17%) patients during ICU admission. Of the 340 ICU survivors, 292 remained in the same hospital. Of these, 96 (33%) received a pharmacological sleep aid at least once during their post‐ICU general hospital ward stay. Pre‐hospital sleep aid use, male sex, longer ICU admission and higher APACHE (Acute Physiology and Chronic Health Evaluation) III scores were associated with sleep aid prescription in the ICU. Conclusions: Pharmacological sleep aids are administered frequently in the ICU with administration increasing substantially after ICU discharge.